Augmented reality objects design in augmented story book mobile application for better engagement - Sherina Izzaty; Herman Tolle; Rizdania Dermawi; Frihandhika Permana (Institute of Advanced Engineering and Science, 2019)
The folktale is a kind of story that has some good points, such as developing a sense of story and shaping up positive attitudes towards children. However, people seem to abandon those good points and often give the children smartphones instead of folktale through the conventional book. Recently, smartphones’ capabilities have rapidly improved, so that augmented reality (AR) story books which combine conventional book and smartphone can be developed. This research is conducted to examine which one from three provided models that work best for engagement in a folktale augmented book. Those designs will be discussed in both subjective and objective approach, correspondingly. The result from subjective approach is the animated video AR design becomes the most pleasing design. The picture and narrator’s voice AR design, by contrast, becomes the most efficient design based on objective approach.